10th Independent Science Panel Meeting, 30 May 2016 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
In May 2016 the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) held its tenth Independent Science Panel meeting in a virtual space.